(untitled) (Itinera, 2023)
During the nineteenth century the theatre building - and in particular the opera house - imposed itself as tangible proof of the civic progress of Western societies. As Mazzini theorised the “civilization of the multitudes” through the arts, the theatre became the place where this yearning could be pursued. The momentum of Italian theatre construction was impressive during the nineteenth century, both in the major centres and in the small provincial towns. Rome, from this point of view, represents a significant exception. Until the end of the 19th century, the city, although equipped with important venues of the old regime, did not have an opera house conceived in contemporary terms. To fill the gap, for about a century and a half, designers from different backgrounds will work to equip the capital with an opera house worthy of its aspirations. Drawing on rare or little-known sources, produced among others by architects Pietro Sangiorgi, Antonio Lovatti, and Marcello Piacentini, the contribution reflects on the positioning of a large opera house in the urban layout of the capital. From the papal Rome and the liberal age, to the fascist period, the longed opera house tries to give new, contemporary meanings to a building that will come to stand out for its fascinating outdatedness.